Legal Compliance Analysis of the BPJS Health Patient Referral Procedures at Primary Healthcare Facilities - Widya; Prayuti, Yuyut (LifeSciFi, 2025)
This study analyzes the BPJS Health referral procedure at the Kimia Farma Sumber Cirebon Clinic through an empirical qualitative approach. Data were collected through interviews, observations, and documentation studies to evaluate legal compliance, identify driving and inhibiting factors, and formulate recommendations for improvement. Findings indicate that, normatively, the clinic has complied with BPJS regulations, as demonstrated by staff’s good understanding of doctors’ authority and the use of the P-Care system. However, implementation in the field faces technical obstacles, such as the instability of the P-Care system, which triggers the use of temporary referral letters, as well as information gaps that cause patient confusion. It was concluded that legal compliance depends not only on normative compliance, but also on infrastructure support and effective communication. Strategic recommendations focused on three pillars: strengthening technological infrastructure, increasing human resource capacity through continuous training, and improving transparency and patient education on procedures to create synergy between legal compliance, service efficiency, and public accountability within the JKN framework.